2013
DOI: 10.18632/aging.100599
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of Drosophila Sir 2 extends life span in a dose-dependent manner

Abstract: Sir2, a member of the sirtuin family of protein acylases, deacetylates lysine residues within many proteins and is associated with lifespan extension in a variety of model organisms. Recent studies have questioned the positive effects of Sir2 on lifespan in Drosophila. Several studies have shown that increased expression of the Drosophila Sir2 homolog (dSir2) extends life span while other studies have reported no effect on life span or suggested that increased dSir2 expression was cytotoxic. To attempt to reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
80
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 14 publications
3
80
0
Order By: Relevance
“…4C), using the conditional inducible GeneSwitch system, was able to extend life span, with flies fed the gene-activating drug RU486 outliving a genetically identical control cohort fed only the diluent control EtOH. Together with previously published data (21,25), these observed life span extensions suggest a coordinated response integrating maintenance of heterochromatin structure, TE suppression, and longevity.…”
Section: Genetic Interventions That Affect Heterochromatin Structure supporting
confidence: 86%
See 2 more Smart Citations
“…4C), using the conditional inducible GeneSwitch system, was able to extend life span, with flies fed the gene-activating drug RU486 outliving a genetically identical control cohort fed only the diluent control EtOH. Together with previously published data (21,25), these observed life span extensions suggest a coordinated response integrating maintenance of heterochromatin structure, TE suppression, and longevity.…”
Section: Genetic Interventions That Affect Heterochromatin Structure supporting
confidence: 86%
“…In addition to their effects of delaying age-related heterochromatin gene and TE silencing loss, both increased Sir2 expression and decreased Adar expression have been shown to extend life span in flies (21,25), whereas Dicer-2 and Ago2 mutants are short-lived (15,24). Given our findings presented earlier, we examined whether increased expression of Su(var)3-9 or Dicer-2 also have a positive effect on life span.…”
Section: Genetic Interventions That Affect Heterochromatin Structure mentioning
confidence: 91%
See 1 more Smart Citation
“…Importantly, overexpression of Sir2, a histone deacetylase required for heterochromatin formation and gene silencing, induces an increased lifespan in yeast (Kaeberlein et al ., 1999). The connection between heterochromatin maintenance and lifespan extension is further strengthened by studies in Caenorhabditis elegans and Drosophila (Rogina & Helfand, 2004; Hashimoto et al ., 2010; Jiang et al ., 2013; Whitaker et al ., 2013). Disruption of UTX‐1, a histone demethylase that reduces the heterochromatin epigenetic modification called histone H3 K27 trimethylation (H3K27me3), in C. elegans leads to increased H3K27me3 levels and prolonged lifespan (Jin et al ., 2011; Maures et al ., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The yeast SIR2 belongs to class I and is involved in chromatin silencing, DNA damage repair and chromosome condensation during meiosis (Huang et al 2007). In D. melanogaster, it was demonstrated that the increased expression of genes encoding sirtuins may affect the length of their life cycle (Whitaker et al 2013). In C. elegans, four genes have been identified, encoding proteins related to yeast sirtuins.…”
Section: Introductionmentioning
confidence: 99%